Demand function estimate for residential water in Oman. Issue 6 (2nd November 2017) - Kotagama, Hemesiri; Zekri, Slim; Al Harthi, Rahma; Boughanmi, Houcine
Abstract: Current subsidies to residential water users in Oman are estimated at USD 314 million/y. This study estimates the demand function for residential water in Muscat, Oman, for households living in villas. A two-stage least squares econometric model with lagged average water price was used with socio-economic variables. Price elasticity for residential water in Muscat was estimated as –2.10. This high price elasticity is explained by the large proportion of water used for outdoor purposes. This study indicates that it may be possible to manage water demand in Muscat through modifying the price of water and reforming subsidies for residential water.